Comparing two variations of the high‐probability instructional sequence to improve food consumption with a child with autism. (29th July 2018) - Trejo, Mayra J.; Fryling, Mitch J.
Abstract : The present study evaluates the effects of two variations of the high‐probability (Hi P) instructional sequence with a child with autism spectrum disorder. In one variation, the Hi P task was topographically similar to the low‐probability task of food consumption, whereas the second variation involved Hi P tasks that were not topographically similar to the low‐probability task. Results show that both variations of the Hi P sequence were effective at improving consumption and reducing inappropriate mealtime behavior. The participant's mother chose a preferred variation of the Hi P intervention to pursue systematic fading with, the topographically similar Hi P sequence. Consumption remained high and inappropriate mealtime behavior remained low throughout the fading process. Implications for continued research and practice in the area of feeding intervention are provided.